2023
DOI: 10.1093/biolre/ioad024
|View full text |Cite
|
Sign up to set email alerts
|

Compensatory mechanisms in response to induced hypothyroidism in the late gestation pig fetus

Abstract: To understand the effect of fetal thyroid gland disruption on development in swine, we evaluated thyroid hormone levels, growth and developmental characteristics, and gene expression associated with thyroid hormone metabolism in late gestation fetuses exposed to methimazole (MMI). Pregnant gilts were given either oral MMI or equivalent sham from gestation day 85–106 (n = 4/group), followed by intensive phenotyping of all fetuses (n = 120). Samples of liver (LVR), kidney (KID), fetal placenta (PLC) and the corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 71 publications
(99 reference statements)
1
3
0
Order By: Relevance
“…These histological changes in thyroid structure were consistent with pathological signs of goiter seen in rats exposed to MMI (Tsujio et al, 2007) as well as in hypothyroid human patients (Mizukami et al, 1993). Interestingly, the thyroid histology following MMI treatment differed from recent observation in fetal swine which showed a loss of eosinophilic colloid and collapse of thyroid follicle shape, but an undisturbed epithelial structure (Ison et al, 2023). We hypothesize this apparent difference in porcine thyroid response to MMI results from reduced pituitary capacity for TSH production during development of the HPT axis in the prenatal swine.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…These histological changes in thyroid structure were consistent with pathological signs of goiter seen in rats exposed to MMI (Tsujio et al, 2007) as well as in hypothyroid human patients (Mizukami et al, 1993). Interestingly, the thyroid histology following MMI treatment differed from recent observation in fetal swine which showed a loss of eosinophilic colloid and collapse of thyroid follicle shape, but an undisturbed epithelial structure (Ison et al, 2023). We hypothesize this apparent difference in porcine thyroid response to MMI results from reduced pituitary capacity for TSH production during development of the HPT axis in the prenatal swine.…”
Section: Discussionsupporting
confidence: 74%
“…Hypothyroidism has been noted to impact the expression of genes associated with deiodinases in rats, specifically through increased activation (DIO2) and decreased deactivation (DIO3) of thyroid hormone (Gereben et al., 2008 ; Silva & Matthews, 1984 ). Previous work in the fetal swine demonstrated altered hepatic deiodinase gene expression (DIO1, DIO2, DIO3) in response to severe MMI induced hypothyroidism (Ison et al., 2023 ). In contrast the present study found no significant change in hepatic deiodinase expression in response to mild systemic hypothyroidism.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Significant hypothyroidism accompanied by elevated TRH led to hyperprolactinemia, interruption of pulsatile LH secretion, decreased SHBG synthesis, interruption of peripheral estrogen metabolism, and increased ovarian androgen production ( 125 ). In a study of female pigs, hypothyroidism led to increased gonadotropin receptor sensitivity in the ovaries, which ultimately promoted ovarian hypertrophy and the formation of multiple ovarian cysts ( 126 ). Moreover, hypothyroidism may lead to severe and irregular menstrual bleeding, spotting during the menstrual cycle, insufficient endometrial thickness, ovulation disorders, and eventually endometrial hyperplasia disorders ( 127 , 128 ).…”
Section: Analysis Of Potential Thyroid-related Etiologies Of Pcosmentioning
confidence: 99%
“…These effects are consistent with the long-term implications of fetal hypothyroidism in humans, with observed clinical symptoms such as mental retardation [ 10 ], delayed bone development [ 11 ], and poor growth [ 12 ]. As swine are a commonly used biomedical model [ 13 ], the current study utilizes a porcine model of congenital hypothyroidism in which MMI, which we have previously shown to cross the porcine placenta and induce severe fetal hypothyroidism [ 14 ], is used to examine the molecular impact of late gestation hypothyroidism on the developing fetus.…”
Section: Introductionmentioning
confidence: 99%